2016
DOI: 10.1534/genetics.116.191429
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Natural Populations: How Differentially Expressed Genes Shape the Evolution of Chromosomal Inversions inDrosophila pseudoobscura

Abstract: Chromosomal rearrangements can shape the structure of genetic variation in the genome directly through alteration of genes at breakpoints or indirectly by holding combinations of genetic variants together due to reduced recombination. The third chromosome of Drosophila pseudoobscura is a model system to test hypotheses about how rearrangements are established in populations because its third chromosome is polymorphic for >30 gene arrangements that were generated by a series of overlapping inversion mutations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
92
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 84 publications
11
92
2
Order By: Relevance
“…The enrichment of gene expression differences in our study is consistent with patterns found in inversions between chimpanzees and humans (MarquĂšs‐Bonet et al., ) and Drosophila (Fuller et al., ; Said et al., ), but contrasts with results for the plant Boechera stricta (Lee et al., ). While the finding of an enrichment of differential gene expression for inversions in this study and others is consistent with the supergene hypothesis of inversion evolution, it is by no means definitive proof.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The enrichment of gene expression differences in our study is consistent with patterns found in inversions between chimpanzees and humans (MarquĂšs‐Bonet et al., ) and Drosophila (Fuller et al., ; Said et al., ), but contrasts with results for the plant Boechera stricta (Lee et al., ). While the finding of an enrichment of differential gene expression for inversions in this study and others is consistent with the supergene hypothesis of inversion evolution, it is by no means definitive proof.…”
Section: Discussionsupporting
confidence: 91%
“…Global gene expression analyses offer one way to test whether inversions hold together haplotypes of genetic variation potentially responsible for phenotypic divergence between locally adapted populations. Research in a few systems has found evidence of increased levels of expression divergence in inversions (Cassone et al., ; Fuller, Haynes, Richards, & Schaeffer, ; MarquĂšs‐Bonet et al., ). For example, MarquĂšs‐Bonet et al.…”
Section: Discussionmentioning
confidence: 99%
“…In case segregating weakly-deleterious variants had led to a downward bias in estimates of α, we repeated this analysis excluding all alleles with a minor allele frequency <0.125 [44], although this reduced power to the extent that few genes remained individually significant (Additional file 5 Table S3). We also repeated the analysis with a larger dataset PRJNA326536 [45] (Additional file 5 Table S3), and obtained qualitatively similar results (R 2 =0.946 for α estimates between the analyses; the second dataset, while larger, is less suitable for analysis as only the third chromosome is a direct sample from a wild population).…”
Section: Adaptive Amino-acid Substitutions Are Generally More Common mentioning
confidence: 67%
“…; Fuller et al . ; Mack et al . ), transcriptional profiling could constitute a complementary approach to identifying candidate genes that would not be subject to the same limitation.…”
Section: Discussionmentioning
confidence: 99%